Disassembly of the reconstituted synaptic vesicle membrane fusion complex in vitro. - Hayashi, T (1995)
The interaction of the presynaptic membrane proteins SNAP-25 and syntaxin with the synaptic vesicle protein synaptobrevin (VAMP) plays a key role in the regulated exocytosis of neurotransmitters. Clostridial neurotoxins, which proteolyze these polypeptides, are potent inhibitors of neurotransmission. The cytoplasmic domains of the three membrane proteins join into a tight SDS-resistant complex (Hayashi et al., 1994). Here, we show that this reconstituted complex, as well as heterodimers composed of syntaxin and SNAP-25, can be disassembled by the concerted action of the N-ethylmaleimide-sensitive factor, NSF, and the soluble NSF attachment protein, alpha-SNAP. alpha-SNAP binds to predicted alpha-helical coiled-coil regions of syntaxin and SNAP-25, shown previously to be engaged in their direct interaction. Synaptobrevin, although incapable of binding alpha-SNAP individually, induced a third alpha-SNAP binding site when associated with syntaxin and SNAP-25 into heterotrimers. NSF released prebound alpha-SNAP from full-length syntaxin but not from a syntaxin derivative truncated at the N-terminus. Disassembly of complexes containing this syntaxin mutant was impaired, indicating a critical role for the N-terminal domain in the alpha-SNAP/NSF-mediated dissociation process. Complexes containing C-terminally deleted SNAP-25 derivatives, as generated by botulinal toxins type A and E, were dissociated more efficiently. In contrast, the N-terminal fragment generated from synaptobrevin by botulinal toxin type F produced an SDS-sensitive complex that was poorly dissociated.